(untitled) (Qawanin Jurnal Ilmu Hukum, 2023)
Abstract: This study aims to determine the application of the handling of money politics in Bulukumba Regency, which was carried out by the participants of regional head candidates, voters and campaign teams in the regional head elections in Bulukumba Regency. This research was carried out in Bulukumba district by selecting the agency related to this case, namely the Bulukumba Regency General Election Supervisory Agency. The data collection method used is the interview method and the study of documentation then the data obtained were analyzed descriptively qualitatively so as to reveal the expected results and conclusions on the problem. The results of this study indicate that: The implementation of handling violations of money politics by the Integrated Law Enforcement Center (GAKKUMDU) of Bulukumba Regency in the 2020 regional head election has been carried out with the provisions of the flow of handling election violations based on PERBAWASLU No. 8 of 2020 and there are 11 cases of alleged criminal acts of money politics, 1 case which was forwarded to the District Court. Bulukumba, 10 cases were discontinued because they did not meet the alleged elements. Factors influencing the Integrated Law Enforcement Center in dealing with money politics at the General Elections Supervisory Agency of Bulukumba Regency. There are 3 main problems, namely legal substance, legal structure, and legal culture. The recommendation of this research: it is hoped that the candidates for regional heads, campaign teams, voters, and general election organizers will continue to run democratic parties honestly and fairly. Abstrak: Penelitian ini bertujuan untuk mengetahui penerapan penanganan tindak pidana politik uang di Kabupaten Bulukumba, yang dilakukan oleh para peserta calon kepala daerah, pemilih dan tim kampanye pada pemilihan kepala daerah di Kabupaten Bulukumba. Pelaksanaan penelitian di kabupaten Bulukumba dengan memilih instansi yang terkait dengan perkara ini yakni di Badan Pengawas Pemilihan Umum. Metode penelitian Hukum empiris yang digunakan adalah metode wawancara dan studi dokumentasi kemudian data yang diperoleh dianalisis secara deskriptif kualitatif sehingga mengungkapkan hasil yang diharapkan dan kesimpulan. Hasil penelitian penelitian ini menunjukkan bahwa: Pelaksanaan penanganan pelanggaran tindak pidana politik uang oleh Sentra Penegakan Hukum Terpadu (GAKKUMDU) Kabupaten Bulukumba pada pemilihan kepala daerah pada tahun 2020 telah terlaksana dengan ketentuan alur penanganan pelanggaran pemilihan berdasarkan PERBAWASLU No. 8 Tahun 2020 dan terdapat 11 kasus dugaan tindak pidana politik uang 1 kasus yang diteruskan ke pengadilan negeri Kab. Bulukumba, 10 kasus hentikan karena tidak memenuhi unsur yang disangkakan. Faktor-faktor yang mempengaruhi Sentra Penegakan Hukum Terpadu dalam menangani tindak pidana politik uang di Badan Pengawas Pemilihan Umum Kabupaten Bulukumba. Terdapat 3 pokok masalah yakni substansi hukum, struktur hukum, budaya hukum. Rekomendasi penelitian ini: diharapkan para calon kepala daerah, tim kampanye, pemilih, dan penyelenggara pemilihan umum untuk tetap menjalankan pesta demokrasi secara jujur dan adil.